Confronting terrorism : European experiences, threat perceptions, and policies - Leeuwen, Marianne van (Nijhoff law specials, 2003)
This work focuses on terrorism and the struggle against it in Europe - on contemporary experiences, threat perceptions and the policies of several European countries, including the effects produced by the 11 September, 2001 attacks in the US.